Politische Kulturforschung reloaded: Neue Theorien, Methoden und Ergebnisse - Bergem, Wolfgang; Lietzmann, Hans J.; Diehl, Paula (transcript, 2019)
New research findings on the relationship between politics and culture as well as innovative programmatic and methodological approaches to political cultural research.